Agromorphological characterization of cacao (Theobroma cacao L.) accessions from the germplasm bank of the National Institute of Agrarian Innovation, Peru - Vásquez García, Jheiner (2022)
Agromorphological characterization of cacao accessions in Peru is currently an important tool in the conservation and genetic improvement of cacao germplasm. The objective of this study was to carry out the morphological and agronomic characterization of 113 cacao accessions from the Huarangopampa germplasm bank. Tree, leaf, flower, fruit and seed descriptors were used. The data collected were processed by descriptive statistics using multivariate techniques. Five groups were formed according to similar characteristics. The accessions of group 1 are vigorous trees with an pod index of 19.27 pods/kg of seeds; the groups that presented better differential characteristics were group 2 with erect tree architecture, intermediate vigorousness, purple seed color and pod index of 20.07 pods/kg of seeds and group 3, which had the highest number of accessions with the lowest pod index of 18.77 pods/kg of seeds, besides being vigorous trees and having purple seeds. On the other hand, group 4 presented a particular characteristic of white seed color and high pod indexes with 22.11 pods/kg of seeds. Finally, group 5 accessions were characterized by intermediate tree architecture and vigor with an pod index of 21.3 pods/kg of seeds. The morphoagronomic characterization constitutes a first advance in the identification of cacaos with potential for genetic improvement and advances in the Peruvian chocolate industry.